ENHANCING READING COMPREHENSION SKILLS IN ENGLISH THROUGH GAMIFICATION FOR 5th – 7th – GRADE STUDENTS (Multidisciplinary Journal of Science and Technology, 2025)
This study explores the impact of gamification on the reading comprehension skills of 5th–7th grade ESL students. Using a quasi-experimental design, the research compares an experimental group, which engaged in gamified reading activities, with a control group that followed traditional methods. The results show that the experimental group demonstrated a 25% improvement in comprehension scores, while the control group improved by only 10%, proving the effectiveness of gamification.